Survivors : stories of those left behind by suicide - Tan, Tam Mei (2015)
This is a feature writing journalism project about survivors of suicide - the family and friends of a suicide victim. A recent report from the SOS (published in The Straits Times) showed that a number of people who have lost someone to suicide tend to have suicidal thoughts themselves. We found this worrying and felt that there needs to be more concern and support for this group of people. Suicide in our society still remains a huge stigma, and we hope that our project will help to create more conversation about what else needs to be done for these survivors. More importantly, those with similar experiences might realise they are not alone in their grief, and not be afraid to come forward to seek help.